Assessing the success of mine restoration using Hemiptera as indicators - Orabi, Gamal; Moir, Melinda; Majer, Jonathan (CSIRO Publishing, 2010)
Understanding trends in assemblage composition of key invertebrate groups can provide important insight into the ‘condition’ of, or changes in, the environment. Species density, abundance and composition of Hemiptera (true bugs) were assessed in jarrah (Eucalyptus marginata) forest and a chronosequence of restored bauxite mine pits near Boddington, Western Australia, in order to evaluate how restoration was progressing. A significant difference was uncovered for hemipteran species density between the youngest restored treatment and forest. In contrast, hemipteran composition was distinct between the forest and all restored treatments. Hemipteran composition was associated with the presence of the plant species Conostylis setigera and Trichocline spathulata, and plant structure between 160–180 cm and 260–280, plus soil pH. Restoration was successful in returning Hemiptera with respect to species density, but restoration was yet to attain a similar composition of Hemiptera to that of unmined forest, despite some of the restored sites being almost 20 years old. These results are similar to those of other studies that have assessed the response of Hemiptera to disturbance, and highlight the need to wait for considerable periods in order to achieve restoration goals. This study also confirms the utility of Hemiptera as bioindicators of environmental ‘condition’ and change.